Foreign Trade and Tariff Proposals. hearings before the United States House Committee on Ways and Means, Ninetieth Congress, second session, on June 11-13, 1968. (U.S. Congressional Hearings., 1968)
Continuation of hearings on H.R. 17551, the Trade Expansion Act of 1968, and related bills to amend the Trade Expansion Act of 1962 and the Tariff Act of 1930. Focuses on agricultural products in international trade.